A small town in the early apartheid era: A history of Grahamstown 1946-1960 focusing on "White English" perspectives. - Lancaster, Rupert Giles Swinburne (Rhodes University, Faculty of Humanities, Department of History, 2013)
This Thesis examines the socio-political perceptions of Grahamstown, a small South African City, during the period 1946 to 1960. The 'White English' population of Grahamstown is the specific focus, as it formed the dominant social group during the period and consequently provided the majority of information for this work. During this period the majority of Grahamstowns 'White English' population thought of their City as holding many attractive features and experiences despite the slum-conditions and poverty that were rife in the Locations. During the British Royal Familie's tour of the Union of South Africa in 1947, Grahamstown was one of the Cities visited. The loyalty that Grahamstown's 'White English' citizens felt towards the Royal Family and the United Kingdom is explored in connection with the regard that 'White English' Grahamstown held for the 1820 Settlers. To highlight the Grahamstown City Council's activities during this period five events are analysed: The Grahamstown Financial Crisis, The Grahamstown Housing Crisis, The Beer Hall Debate, The establishment of a Tuberculosis Hospital and the granting of Full University Status to Rhodes University College. It is shown, with regard to the politics of the period, that 'White English' Grahamstown, unequivocally supported the United Party and were vocally anti-Nationalist. The implementation of Apartheid policies within Grahamstown is explored, with specific focus placed upon the Group Areas Act. Finally the anti-republican sentiment espoused by 'White English' Grahamstown is reviewed.
Keywords: Grahamstown (South Africa) -- History -- 20th Century; Grahamstown (South Africa) -- Politics and government -- 20th century; Grahamstown (South Africa) -- Social conditions -- 20th Century; Grahamstown (South Africa) -- Economic conditions -- 20th Century; Grahamstown (South Africa) -- Social life and customs -- 20th Century; Apartheid -- South Africa; Whites -- South Africa -- Grahamstown